Experimental Assessment of Various Batteries and Propellers for Small Solar-Powered Unmanned Aerial Vehicle - Rajendran, Parvathy; Smith, Howard (ITB Journal Publisher, LPPM ITB, 2018)
In this study, the performance of the propulsion system of a solar-powered unmanned aerial vehicle (UAV) was investigated. Both battery and propeller variation tests were performed to evaluate their performance in relation to an electric motor. The battery was varied in the number of cells and capacity, and the propeller was varied in terms of diameter, pitch, manufacturer, and propeller type (fixed and folding propellers). For validation, the bench test result was compared with a simulation model. The bench test provided a reasonable guide for the throttle level required to obtain optimal power. A large variation existed in propeller performance between manufacturers. Sizing electric propulsion is important for UAV performance and the manufacturing factor is significant for propeller performance.